DAMPAK COVID-19 TERHADAP PERUBAHAN HARGA DAN RETURN SAHAM - Novi Darmayanti; Titik Mildawati; Fitriah Dwi Susilowati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2020)
ABSTRACTCOVID-19 is an acronym for “Corona Virus Desease-2019”. Emergance at the end of 2019 and the explosion of this virus caused by rapid transmission yo the effects caused and the absence of a vaccine that can definitely fight this virus. In Indonesia, the peak of people’s fear of this virus occured when the first COVID-19 case was announced on 2 March 2020. The impact of this outbreak attacked all sectors including the capital market. By using paired sample t test, this study aims to analyze the impact of the announcement on changes in price and stock returns PT. Indosat, Tbk. The results showed that stock prices experienced significant changes with sig.value 0,000 < 0,05 . While stock returns did not change due the announcement because sig.velue of stock return is 0,946 > 0,05.